DIGITALISASI SEKTOR UMKM DAN DAMPAKNYA TERHADAP PERTUMBUHAN EKONOMI DI INDONESIA - Ikhlaszul, Ammar; Satria, Dias (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2023)
Digital marketing communications can be the key to optimizing a business. If MSMEs can develop a digital marketing communication strategy, it is part of the adaptation to survive and thrive in the current situation. In addition, the use of technology makes it easier for businesses to gain market share and consumers. With this being one of the concerns in this study. To find out which indicators of SMEs and technologies can influence the increase in economic growth in Indonesia so that MSME business actors can develop so as to increase national economic growth. By paying attention to this, it can be concluded later that how the MSME business should be developed and able to increase economic growth. By conducting multiple linear regression analysis to find out the development of MSMEs which can influence national economic growth with important aspects that are able to develop MSME businesses to increase economic growth. The results showed that there was influence from each indicator of MSME and technology on the six variables of this study. Overall, each research variable influences economic growth. While partially there is a significant influence both positive and negative. Dengan melakukan analisis regresi linear berganda untuk mengetahui perkembangan UMKM yang dapat memengaruhi pertumbuhan ekonomi nasional dengan aspek penting yang mampu mengembangkan bisnis UMKM untuk meningkatkan pertumbuhan ekonomi. Hasil penelitian menunjukkan bahwa terdapat pengaruh dari setiap indikator UMKM dan teknologi pada keenam variabel penelitian ini. Secara keseluruhan setiap variabel penelitian berpengaruh terhadap pertumbuhan ekonomi. Sedangkan secara parsial terdapat pengaruh yang signifikan baik itu positif maupun negatif.